Phương trình (4+2x).(x-1)=0
A.X=1;X=2
B.X=-2;X=1
C.X=-1;X=2
D.X=1;X=\(\frac{1}{2}\)
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(B=\left(x+\frac{1}{x}\right)^2+\left(y+\frac{1}{y}\right)^2+\left(xy+\frac{1}{xy}\right)^2\)
\(-\left(x+\frac{1}{x}\right)\left(y+\frac{1}{y}\right)\left(xy+\frac{1}{xy}\right)\)
\(\Rightarrow B=x^2+2+\frac{1}{x^2}+y^2+2+\frac{1}{y^2}+x^2y^2+2+\frac{1}{x^2y^2}-x^2y^2\)
\(-2-x^2-y^2-\frac{1}{y^2}-\frac{1}{x^2}-\frac{1}{x^2y^2}\)
\(\Rightarrow B=x^2y^2-x^2y^2+x^2-x^2+1.\frac{1}{x^2}+1.\frac{1}{x^2y^2}-1.\frac{1}{x^2}-1\)
\(.\frac{1}{x^2y^2}+1.\frac{1}{y^2}-1.\frac{1}{y^2}+y^2-y^2+2+2+2-2\)
\(\Rightarrow B=4\)
\(\left(4+2x\right)\left(x-1\right)=0\)
\(\orbr{\begin{cases}4+2x=0\\x-1=0\end{cases}\Rightarrow\orbr{\begin{cases}2x=-4\\x=1\end{cases}\Rightarrow}\orbr{\begin{cases}x=-2\\x=1\end{cases}}}\)
vậy ta chọn : B